PEMETAAN PARTISIPASI GURU PENDIDIKAN JASMANI SMA TERHADAP OLAHRAGA SOFTBALL DI DAERAH ISTIMEWA YOGYAKARTA - Agus Susworo Dwi Marhaendro (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2011)
AbstractThis study has the objective to find a map of the participation of high school physical education teacher of the sport of softball in the Special Region of Yogyakarta. This study is a descriptive type of research with survey methods. Respondents were high school physical education teacher and equal in Yogyakarta as many as 98 people, which is obtained through purposive cluster sampling. The research instrument used was questionnaire made by the participation of researchers, consisting of 13 structured items and unstructured questions. Data collection techniques by approaching each respondent and take it back. Analysis of the data that is used is to use percentages or called percentage correction. The results showed that the physical education teacher is a human resources that could be involved in sports coaching softball, and yet their knowledge and understanding only in part to the involvement of small use, so it already has the capital to participation but have not been able to be maximized becomes an active participation in coaching softball at DIY. Physical education teacher is only a small part that gives information about the sport of softball to the students, so the possibility that students can be involved in the sport of softball. They do not understand the softball games or learning, that learning the game not have to play softball softball itself. PJKR Studies Program, State University of Yogyakarta as the estuary of the physical education teacher participation in DIY insports coaching softball participation in DIYKeywords: Participation, Development, Softball, High School Physical Education Teacher,AbstrakPenelitian ini mempunyai tujuan untuk mengetahui peta partisipasi guru pendidikan jasmani SMA terhadap olahraga softball di Daerah Istimewa Yogyakarta. Penelitian ini merupakan jenis penelitian deskriptif dengan metode survey. Responden adalah guru pendidikan jasmani SMA dan sederajat di Daerah Istimewa Yogyakarta sebanyak 98 orang, yang diperoleh melalui purposive cluster sampling. Instrumen penelitian yang digunakan adalah angket partisipasi yang dibuat sendiri oleh peneliti, yang terdiri dari 13 butir pertanyaan tersetruktur dan tidak terstruktur. Teknik pengumpulan data dengan cara mendatangi setiap responden dan mengambilnya kembali. Analisis data menggunakan. Analisis data yang dipergunakan adalah dengan penggunaan persentase atau disebut procentage correction. Hasil penelitian menunjukkan bahwa bahwa guru pendidikan jasmani merupakan sumber daya manusia yang dapat dilibatkan dalam pembinaan olahraga softball, namun demikian pengetahuan dan pemahaman mereka hanya sebagaian kecil digunakan pada keterlibatan, sehingga modal untuk partisipasi sudah dimiliki tetapi belum mampu dimaksimalkan menjadi partisipasi yang aktif dalam pembinaan softball di DIY. Guru pendidikan jasmani tersebut hanya sebagian kecil yang memberikan informasi tentang olahraga softball kepada para siswa, sehingga menutup kemungkinan siswa dapat terlibat dalam olahraga softball. Mereka belum memahami pembelajaran permaianan softball, bahwa pembelajaran permainan softball tidak harus bermain softball itu sendiri. Program Studi PJKR Universitas Negeri Yogyakarta sebagai muara dari partisipasi guru pendidikan jasmani di DIY dalam partisipasi pembinaan olahraga softball di DIYKata kunci : Partisipasi, Pembinaan Softball, Guru Pendidikan Jasmani SMA